ANALISIS RISIKO KESEHATAN LINGKUNGAN AKIBAT PAPARAN BENZENE MELALUI INHALASI PADA AWAK MOBIL TANGKI DI PT PERTAMINA PATRA NIAGA - Nurtito Wahyu Febrian; Mursid Rahardjo; Nurjazuli Nurjazuli (Jurnal Kesehatan Masyarakat (Undip), 2019)
PT Pertamina Patra Niaga is one of the motor fuel terminal in charge to do the distribution of fuel in Central Java. Fuel distribution in the activities of the workers who called the Car Tank Crew (AMT) should get in touch with benzene's cancer-causing. The purpose of this research was to analyze the health risks of environmental exposure to benzene on AMT. This research is descriptive research with an environmental health risk analysis approach (ARKL). The research sample was 49 respondents AMT and the sample concentration levels of benzene is object (C) in the ambient air of PT Pertamina Patra Niaga. The results showed an average benzene concentration was 0.08 ppm. Average weight (Wb) respondents 66.20 kg, exposure time (tE) 8 hours/day, the frequency of exposure (fE) 243 days/year, and the duration of exposure (Dt) 4 years. Exposure to benzene intake is 0.0024 mg/kg/day for non carcinogenic effects are realtime, 0.021 mg/kg/day for non carcinogenic effects of lifetime, 0.0011 for carcinogenic effects are realtime and 0.009 for carcinogenic effects of lifetime. The characteristics of risk for carcinogenic effects are realtime RQ ≤ 1 i.e. 0.29 and non carcinogenic effects for lifetime RQ > 1 i.e. 2.47. While the carcinogenic effects for realtime on ECR ≤ 10-4 IE 6.05 x 10-5 and carcinogenic effects for a lifetime on ECR 10-4 > i.e. 4.95 x 10-4. Conclusion of this research is the concentration of benzene in ambient air of PT Pertamina Patra Niaga was still under the threshold and not show health problems to exposure to realtime will be but estimated there is a risk of exposure to health disorders lifetime of 30 years.